(untitled) (Spagna contemporanea. Rivista semestrale di storia, cultura, istituzioni, 1999)
Margherita Sarfatti e la Spagna mistica Margherita Sarfatti was one of the builders of the first phase Fascism’s ideology and of the régime’s stabilisation process. Her trip to the Spain of Primo de Rivera, and her analysis of his potential fascistisation, gave way to hypothesis of relationships between the two powers. The reasons of the analogy between the two Countries and the possible agreement of Italy and Spain about a similar State’s model, are explained in her writings by the arts and Catholicism’s role, held together by a symbolic unifying strength which for her has the goal of strengthening Fascism’s cultural and thus political.